Clinical Findings and Prognostic Factors for Dogs Undergoing Cholecystectomy for Gall Bladder Mucocele. Issue 4 (17th January 2013) - Malek, Sarah; Sinclair, Elizabeth; Hosgood, Giselle; Moens, Noel M. M.; Baily, Trina; Boston, Sarah E.
<x xml:space="preserve">Abstract</x> Objective To report clinical findings and explore prognostic factors for dogs that had cholecystectomy for gall bladder mucocele. Study Design Retrospective case series. Animals Dogs (n = 43) with gall bladder mucoceles. Results Diagnosis of gall bladder mucoceles was confirmed by histopathology and 74% were diagnosed based on preoperative abdominal ultrasonography. Intraoperative evidence of gall bladder rupture was noted in 10 dogs (23%), and 16 (37%) had evidence of previous leakage in the abdominal cavity. One dog had positive bacterial growth from the gall bladder content. The most common histopathologic findings in liver biopsies obtained at surgery were cholangiohepatitis, biliary hyperplasia, or cholestasis. Univariate analysis showed evidence of postoperative hypotension (P = .05) to be significantly negatively associated with survival. Significant difference in mean postoperative serum lactate (P = .034) and postoperative packed cell volume (P = .063) between dogs that survived and died was also noted. Conclusions Elevations in postoperative serum lactate concentrations and immediate postoperative hypotension in dogs undergoing cholecystectomy for gall bladder mucoceles are associated with poor clinical outcome.